PROFESSOR P. R. KIRBY. An excellent bibliography of the works of Professor Percival R. Kirby, a pioneer in the field of African music studies in South Africa, has recently been published by the Johannesburg Public Library, compiled by Valerie Bryer, B. Mus, as part of her fulfilment of the requirements for the Diploma in Librarianship. (International Library of African Music, 1965)
pages: 87
Keywords: South Africa; African Music